Combined simulation of fatigue crack nucleation and propagation based on a damage indicator - M. Springer; M. Nelhiebel; H. E. Pettermann (Fracture and Structural Integrity)
Fatigue considerations often distinguish between fatigue crack nucleation and fatigue crack propagation. The current work presents a modeling approach utilizing one Fatigue Damage Indicator to treat both in a unified way. The approach is implemented within the framework of the Finite Element Method. Multiaxial critical plane models with an extended damage accumulation are employed as Fatigue Indicators. Locations of fatigue crack emergence are predicted by these indicators and material degradation is utilized to model local material failure. The cyclic loading is continued on the now degraded structure and the next location prone to material failure is identified and degradation modeled. This way, fatigue crack propagation is represented by an evolving spatial zone of material failure. This propagating damage zone leads to a changing structural response of the pristine structure. By recourse to the Fatigue Damage Indicator a correlation between the number of applied load cycles and the changing structural behavior is established. Finally, the proposed approach is exemplified by cyclic bending experiments in the Low Cycle Fatigue regime.